Arabidopsis MSI1 functions in photoperiodic flowering time control - Steinbach, Yvonne; Hennig, Lars (Frontiers in Plant Science, 2014)
Appropriate timing of flowering is crucial for crop yield and the reproductive success of plants. Flowering can be induced by a number of molecular pathways that respond to internal and external signals such as photoperiod, vernalization or light quality, ambient temperature and biotic as well as abiotic stresses. In several plant species, such as Arabidopsis, tomato, tobacco and rice, it has been shown that the key florigenic signal FLOWERING LOCUS T (FT) moves from the leaves, where photoperiod is sensed, to the shoot apex, where the FT protein induces the switch to flowering. FT is regulated by several flowering activators, such as CONSTANS (CO), and repressors, such as FLOWERING LOCUS C (FLC). CONSTANS in turn, must be expressed in a specific diurnal pattern to allow FT activation in Arabidopsis under long day but not under short day photoperiods. Chromatin modifications are essential for regulated gene expression, which often involves members of the well conserved MSI1-like protein family. MSI1-like proteins are ubiquitous partners of various complexes, such as POLYCOMB REPRESSIVE COMPLEX 2 (PRC2) or CHROMATIN ASSEMBLY FACTOR 1 (CAF1). In Arabidopsis, five MSI1-like proteins exist. One of their functions is to control the switch to flowering. MSI4/FVE is proposed to be associated with a HDAC complex to repress the floral repressor FLC and MSI1 is needed for the correct expression of the floral integrator gene SUPPRESSOR OF CO 1 (SOC1). Here, we show that the histone-binding protein MSI1 acts in the photoperiod pathway to regulate normal diurnal expression of CO and to rapidly induce flowering in long day photoperiods. Reduced expression of CO in msi1-mutants leads to failure of FT and SOC1 activation and to delayed flowering. Finally, genetic analyses demonstrated that MSI1 functions upstream of the CO-FT pathway to enable an efficient photoperiodic response.